Integrasi Hadis Kebersihan dalam Kegiatan Piket Kelas untuk Membentuk Karakter Peduli Lingkungan Siswa SD SDIT Syahiral ‘Ilmi Kota Bukittinggi - Yasmiar Yasmiar (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the integration of cleanliness-related hadiths into classroom picket activities to foster environmental care character among students at SDIT Syahiral 'Ilmi Bukittinggi. Using a qualitative case study approach, data were collected through observations, interviews, and documentation involving fourth-grade students and teachers. The integration process included reciting hadiths, reflective discussions, and teacher role modeling. Results indicated that students developed a stronger awareness of cleanliness as a religious obligation, leading to proactive participation in maintaining classroom hygiene. Behavioral improvements, such as spontaneous cleanliness initiatives and peer collaboration, were observed. The study concludes that embedding Islamic teachings into routine school activities effectively cultivates environmental consciousness rooted in faith. Recommendations include expanding this model to other Islamic schools and enhancing teacher training for holistic character education.